A new species of Okanagana native to a unique serpentine ecosystem in Northern California (Hemiptera: Auchenorrhyncha: Cicadidae) - Smeds, Elliott A.; Chatfield-Taylor, Will (Zootaxa, 2025)
Okanagana monochroma sp. nov. is described from a unique and geographically isolated serpentine ecosystem in Northern California. The new species is diagnosed from other Okanagana Distant by a combination of morphological and bioacoustic characters. We provide a description of the calling song, habitat, and host plant associations of O. monochroma sp. nov., and present hypotheses for possible endemism models to explain its remarkably narrow geographic range, which may be the smallest of any North American cicada.